Revision of the Botanophila helviana species group (Diptera: Anthomyiidae) in Europe - Michelsen, Verner (Zootaxa, 2009)
Species of the Botanophila helviana species group are small, blackish anthomyiids known from temperate to subarctic (northern/elevated) parts of the Holarctic Region. Adult flies are anthophilous, obtaining pollen and nectar from various flowering plants. Preliminary evidence suggests that the larvae may attack developing seed heads of Ranunculus (Ranunculaceae). The male and female terminalia are very characteristic and support the monophyly of the species group. Further evidence for this is provided by the peculiar structure of their prestomal teeth. A taxonomic revision of the European species with illustrated descriptions and an identification key to males and females is given. The following six species are treated: Botanophila helviana Michelsen, 1983, B. kitadakeana Suwa, 1998 and the new species B. minuta (Norway, Sweden), B. nigra (Norway, Finland and Sweden), B. peristeriensis (Greece) and B. saliciphila (Spain).